POTENSI PENATAAN PARKIR DI KABUPATEN BANDUNG - Mahardika, Kani (Universitas Komputer Indonesia, 2020)
Growth in population accompanied by economic growth has led to an increase in the intensity of the activities of a city, which must be balanced with the provision of urban facilities and infrastructure capable of accommodating this development, in this case the Bandung Regency has experienced the development of activities centers that have an impact on the number parking especially on street parking. This activity resulted in changes in the function of the road and the traffic was hampered so a study was needed to determine the characteristics and needs of parking spaces in Bandung Regency. The purpose of this study was to determine the characteristics of parking and parking space requirements. In general, the method is done by collecting secondary data and primary data. Secondary data needed in this study are related policies and data that support survey location information obtained from the Bandung Regency Transportation Agency (Dishub), while primary data is obtained by field survey. The results of the study show the characteristics of parking in Bandung Regency is dominated by parking on a road or on street with the type of parking perpendicular to the road or parallel to the road (vertical). The road space parking space capacity in Bandung Regency is 570 SRP for cars and 606 SRP for motorcycles. While the demand for road space parking space in Bandung Regency is 3,373 SRP / day for cars and 14,197 / day SRP for motorcycles, in the future it will be necessary to add parking pockets especially with off-street type to reduce illegal parking which causes traffic jams. Keywords: Parking lot, parking arrangement, parking space